Proximal Tibial Anterior Closing Wedge Osteotomy in Repeat Revision of Anterior Cruciate Ligament Reconstruction. (August 2014) - Sonnery-Cottet, Bertrand; Mogos, Stefan; Thaunat, Mathieu; Archbold, Pooler; Fayard, Jean-Marie; Freychet, Benjamin; Clechet, Julien; Chambat, Pierre
Background: Physicians should consider an increased posterior tibial slope (PTS) as a risk factor for graft failure when proposing anterior cruciate ligament (ACL) re-revision. Purpose: To describe the surgical technique of combined ACL revision and proximal tibial anterior closing wedge osteotomy and to evaluate its clinical outcome in cases of recurrent graft failure with associated increased tibial slope. Study Design: Case series; Level of evidence, 4. Methods: Between 2008 and 2010, 5 combined ACL re-revisions with proximal tibial anterior closing wedge osteotomy were retrospectively evaluated after a mean 31.6 months' follow-up (range, 23-45 months). All patients reported subjective knee instability preoperatively and demonstrated increased laxity on physical examination. Intrinsic risk factors for graft failure (excessive tibial slope) were identified in all cases. Preoperative and postoperative functional assessments included the International Knee Documentation Committee (IKDC) score along with the Lysholm score and Tegner activity scale. Results: The mean Lysholm score was 46.2 preoperatively (range, 26-69) and 87.8 (range, 60-100) postoperatively. The mean IKDC subjective score was 39.5 (range, 21.8-64.4) before surgery and 79.1 (range, 48.3-98.9) at the last follow-up. The mean Tegner activity score was 7.4 (range, 5-9) before the latest ACL injury and 7.2 (range, 5-9) at the last follow-up. The mean PTS was 13.6° (range, 13°-14°) preoperatively and 9.2° (range, 8°-10°) postoperatively ( P = .0005). The mean differential anterior laxity was 10.4 mm (range, 8-14 mm), and this significantly decreased to 2.8 mm (range, 2-4 mm) at the last follow-up. Using the Kellgren-Lawrence classification to evaluate the presence of arthritis, 1 patient was grade 1, 3 patients were grade 2, and 1 patient was grade 3. Conclusion: Combined ACL re-revision with proximal tibial anterior closing wedge osteotomy restores knee stability and function with satisfactory clinical outcomes in patients who experience recurrent ACL ruptures with an associated increased PTS.